Additional species of Inocybe (Agaricales, Inocybaceae) from Indonesia - Atik Retnowati; Dewi Susan; Rini Riffiani; Indriati Ramadhani; Iwan Saskiawan (Jurnal Mikologi Indonesia, 2022)
Three species of Inocybe are newly reported from three different locations in Indonesia (Bogor Botanical Garden, Haurbentes (West Java), and Mt. Seraya (Bali)).  Complete descriptions of Inocybe assimilata Britzelm., Inocybe hydrocybiformis (Corner & E. Horak) Garrido, and Inocybe  cf. viraktha K. P. D. Latha & Manim. are provided.  Inocybe assimilata is a member of Inosperma clade, meanwhile I. hydricybiformis and I. cf. varaktha are members of Inocybe clade. Art line of basidiomata and microscopic features, photos of basidiomes, SEM images of basidiospores and cystidia are presented.